Traumas maxilofaciais em vítimas de violência interpessoal periciadas no Instituto Médico Legal de Belo Horizonte - Minas Gerais - Luiza Valeria de Abreu Maia (2013)
The maxillofacial trauma is a very specific type of trauma that occurs in cases of traffic accidents or interpersonal violence. The increase of violence in the cities is one of the causes of maxillofacial trauma that represents an impact on social, psychological and professional victims lives and is one of the biggest challenges of the public health services because of its high incidence and financial costs. This study evaluated the prevalence of maxillofacial trauma in people victims of physical aggression examined at the Institute of Forensic Medicine of Belo Horizonte, Minas Gerais, Brazil. The socio-demographic data (age, sex, residence, occupation, marital status) and maxillofacial trauma patterns (trauma type, side and region of the face affected, instrument used, time of the occurrence and result of the event) were extracted from medical and dental records realized at 2011 year at the Institute of Forensic Medicine. The results were analyzed using the Chi-square test and Bivariate analysis with Bonferronis Correction, with a probability of significance of 5% (p .05). A total of 1956 records were analyzed. The people more affected by maxillofacial injuries were males (p <0.0001), young adults (20-39 years) (p <0.0001), living in Belo Horizonte (p <0.0001), without partner (p <0.0001) and working with delivery service (p <0.0001). The majority of physical agression used the body or parts of it (p <0.0001), occurred during the night (p = 0.006), affected the left side of the face (p <0.0001) and multiple regions (p <0, 0001), causing trauma of soft tissues (p <0.0001), and featuring as crime of body injury" (p <0.0001). It is necessary to monitor the levels of violence through the prevention and education programs to reduce the interpersonal violence and consequently the maxillofacial trauma.